Lullaby raft - Nye, Naomi Shihab 1952-; Nye, Naomi Shihab 1952- (Simon & Schuster Books for Young Readers, 1997)
When the sun goes down, Mama sings a lullaby which tells of animals getting ready for the night
When the sun gîs down, Mama sings a lullaby which tells of animals getting ready for the night
Keywords: Lullabies; Night / Fiction; Animals / Fiction; Animals / Songs; Night / Songs; Night / Juvenile fiction; Lullabies / Juvenile fiction; Night; Wiegenlied; Englisch; Kinderlyrik; USA; Bilderbuch